2022
DOI: 10.1063/5.0085960
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of chaotic system based on image encryption through fractal-fractional operator of non-local kernel

Abstract: In this paper, the newly developed fractal-fractional differential and integral operators are used to analyze the dynamics of chaotic system based on image encryption. The problem is modeled in terms of classical order nonlinear, coupled ordinary differential equations that are then generalized through fractal-fractional differential operator of Mittag-Leffler kernel. In addition to that, some theoretical analyses, such as model equilibria, existence, and uniqueness of the solutions, have been proved. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…After replacing the time fractional operator of FFD, Equations ( 7), (8), and (9) will transformed to:…”
Section: Fractal-fractional Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…After replacing the time fractional operator of FFD, Equations ( 7), (8), and (9) will transformed to:…”
Section: Fractal-fractional Modelmentioning
confidence: 99%
“…The authors concluded that, fractal dimension provide larger memory effects than the usual fractional derivative. Similar articles on the applications of fractal‐fractional theory can be found in [5–10].…”
Section: Introductionmentioning
confidence: 98%
“…In additions, the said area have been used increasingly to investigate various viral infectious diseases including Hepatitis B, and others in [12,13,28,29]. Moreover some interesting applicable in fluid mechanics, vegetable oil process, electromagnetic theory, pine wilt disease can be read in the cited articles as [1,16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Since the advent of integer derivatives, research on fractional-order derivatives has been conducted. This idea has gained a lot of acceptance over the past three decades 40 44 , and it is no longer just applicable to mathematics. Fractional derivatives are the standardization of classical derivatives.…”
Section: Introductionmentioning
confidence: 99%